2011
DOI: 10.12659/msm.881380
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma diagnosed by capsule endoscopy and double balloon endoscopy

Abstract: SummaryBackgroundRenal cell carcinoma commonly metastasizes to lung, liver, and bone. Small intestinal metastases are exceedingly rare.Case ReportA 75-year-old man presented at our hospital with tarry stools. He had undergone a right nephrectomy for renal cell carcinoma (RCC) 6 years previously; in addition, he had received antiplatelet treatment for ischemic heart disease. Esophagogastroduodenoscopy, total colonoscopy, and computed tomography did not identify any cause for the gastrointestinal bleeding. He un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Previous animal and human studies of occlusion balloon devices have reported balloon placement times of 18 min or longer (11)(12)(13). In this study, the maximum time required for balloon placement was only 12 min.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous animal and human studies of occlusion balloon devices have reported balloon placement times of 18 min or longer (11)(12)(13). In this study, the maximum time required for balloon placement was only 12 min.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies which used miniature endoscopes to place infiatable balloons in the bowel have demonstrated the safety of such procedures (11)(12)(13)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Using the combination of CE and DBE, it is possible to obtain clear endoscopic images of the lesions and histological diagnosis prior to the patient undergoing surgery. CE is a reliable approach to such screening, and DBE is an effective approach to the histological diagnosis of small intestinal neoplasms (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…They may behave as the leading point for an intestinal obstruction and intussusceptions. Periampullary region, duodenum and jejunum rank the most common sites .Yet, other sites as large bowel may be involved too (Eo et al, 2008;Loualidi et al, 2004;Nozawa et al, 2003;Papachristodoulou et al, 2004;Roviello et al, 2006;Sadler et al, 2007Takeda et al, 2011. The above cases highlight the importance of considering RCC metastasis as a source of intestinal bleeding and/or obstruction, especially in patients with a known cancer history.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%